2020
DOI: 10.1002/jee.20310
|View full text |Cite
|
Sign up to set email alerts
|

Divergent thinking and academic performance of students with attention deficit hyperactivity disorder characteristics in engineering

Abstract: Background Creativity is increasingly recognized as an important skill for success in the field of engineering, but most traditional, post‐secondary engineering education programs do not reward creative efforts. Failing to recognize creativity or creative efforts can have particularly negative effects for those students with attention deficit hyperactivity disorder (ADHD), who may exhibit enhanced divergent thinking ability yet struggle in the traditional educational environment. Purpose/Hypothesis This study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
36
2
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(51 citation statements)
references
References 100 publications
2
36
2
2
Order By: Relevance
“…Thus, we examine how daily EF interact with Gf and Gc to predict verbal and figural divergent thinking. Given that previous studies assessing the behavioral concomitants of poor EF have found that they are positively related to creativity (Boot et al, 2017;Taylor, Esmaili Zaghi, et al, 2020;Zabelina et al, 2014), we expect to find a positive association between low EF and divergent thinking (Hypothesis 1). However, the relationship between one indicator of EF (i.e., latent inhibition) and divergent thinking has been shown to depend on IQ (Carson et al, 2003;K eri, 2011) and it has been suggested that this may be the case for EF in general (e.g., Boot et al, 2017).…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…Thus, we examine how daily EF interact with Gf and Gc to predict verbal and figural divergent thinking. Given that previous studies assessing the behavioral concomitants of poor EF have found that they are positively related to creativity (Boot et al, 2017;Taylor, Esmaili Zaghi, et al, 2020;Zabelina et al, 2014), we expect to find a positive association between low EF and divergent thinking (Hypothesis 1). However, the relationship between one indicator of EF (i.e., latent inhibition) and divergent thinking has been shown to depend on IQ (Carson et al, 2003;K eri, 2011) and it has been suggested that this may be the case for EF in general (e.g., Boot et al, 2017).…”
mentioning
confidence: 82%
“…However, research assessing daily EF (i.e., self-reports of behavior that reflect individual differences in EF ability) point to an association between poorer EF and creativity. Several studies using self-report assessments of ADHD symptoms in non-clinical samples (e.g., college students) have found that scores are positively related to self-reported creative achievement, behavior, and divergent thinking performance (Boot, Nevicka, & Baas, 2017;Taylor, Esmaili Zaghi, Kaufman, Reis, & Renzulli, 2020;Zabelina, Condon, & Beeman, 2014). For example, Boot et al (2017) found that college students' scores on the ADHD DSM-IV rating scale for adults (Kooij et al, 2005) positively predicted self-reported creative behavior and achievement, as well as originality on a problem construction task asking participants to redefine an everyday problem.…”
mentioning
confidence: 99%
“…Understanding both the challenges and strengths of students with ADHD characteristics and executive functioning difficulties is necessary to create a more holistic view of learners and provide insights into how we can best support students that may not fit into the standard definition of “normal” cognitive functioning. Therefore, the purpose of this study was to better understand the relationship between ADHD characteristics and executive functioning difficulties, divergent thinking, and academic performance by conceptually replicating and expanding on a recent study ( Taylor et al, 2020b ) that found that ADHD characteristics negatively predicted major grade point average (GPA) and positively predicted figural divergent thinking in engineering students.…”
Section: Introductionmentioning
confidence: 96%
“…These characteristics and executive functioning difficulties correspond with poorer academic outcomes for college students, even in cases where students do not meet the diagnostic criteria for ADHD ( Biederman et al, 2006 ; Petersen et al, 2006 ; Norwalk et al, 2009 ; Munro et al, 2017 ). However, these characteristics have also been found to correspond with enhanced performance on divergent thinking tasks, which assess one’s ability to generate many original responses to a stimulus ( Zabelina et al, 2014 ; Boot et al, 2017 ; Taylor et al, 2020b ). Understanding both the challenges and strengths of students with ADHD characteristics and executive functioning difficulties is necessary to create a more holistic view of learners and provide insights into how we can best support students that may not fit into the standard definition of “normal” cognitive functioning.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Cech and Waidzunas (2011) revealed conflicts in which LGBTQ students would pass or cover to cope with and navigate heterodominant environments. Current research is expanding this work by exploring the professional identity formation of groups typically not included nor explicitly addressed in engineering education research such as trans, nonbinary, and gender‐nonconforming individuals (Haverkamp et al, 2019) and individuals with disabilities (McCall et al, 2020; Pearson Weatherton et al, 2017; Taylor et al, 2020). By bringing marginalized voices to the forefront of our work, we can challenge existing sociocultural norms that constrain conceptions of what engineering is and who can enter the profession.…”
Section: Introductionmentioning
confidence: 99%